The Effect of Relationships and Working Conditions on Employee Job Satisfaction at the Department of Trade and Industry in Gowa Regency - Hasmida (Journal AGENCY, 2022)
This study aims to determine the effect of working relations and working conditions on job satisfaction at the Trade and Industry Office in Gowa Regency. The type of research used in this research is a quantitative approach with multiple linear regression analysis models. The results of multiple linear regression which are processed and analyzed using the SPSS method, the equation Y = 1.410 + 0.771.X1 + 0.151.X2 is obtained where the number shows a = 1.410, this figure shows that without a work relationship and working conditions it will affect job satisfaction. b1x1 = 0.771, this means that the work relationship has an effect on job satisfaction. b2x2 = 0.151, this shows that working conditions have an influence on job satisfaction.